Palm Oil Fuel Ash: Promising supplementary cementing materials - Bamaga, S.; Hussin, M.; Ismail, Mohamed (Springer, 2013)
Palm Oil Fuel Ash (POFA) is by-product obtained by burning of fibers, shells and empty fruit bunches as fuel in palm oil mill boilers. In this investigation, three ashes were collected from different palm oil mills around Malaysia and namely CAPOFA, ALPOFA and KTPOFA. The ashes were ground to 45 µm before replace 20% by weight of cement in concrete and mortar. The compressive strength of concretes containing POFA was tested at ages of 7, 28 and 90 days. For durability aspects, concretes and mortars were prepared to investigate the chloride and sulfate resistance respectively in accordance with appropriate ASTM standards. Rapid Chloride Penetration Test (RCPT) was conducted in accordance with ASTM C1202 to investigate the ability of concretes containing POFA to resist the penetration of chloride ions. Change in length and microstructure study for mortar bars containing POFA immersed in sodium sulfate were conducted to evaluate the effects of sulfate attack on POFA mortars. Concrete and mortar specimens were prepared using plain portland cement in order to use as control specimens. At age of 90 days, the results of compressive strength of all POFA concretes were higher than control concrete. All concretes containing POFA showed higher potential to resist chloride ions penetration compared to control concrete. All mortar bars containing POFA showed lower expansion and less porous structure than control mortar. Depending on the results of this investigation, it could be concluded that POFA could be successfully used as supplementary cementing materials to replace 20% of cement in concrete and mortar. © 2013 Korean Society of Civil Engineers and Springer-Verlag Berlin Heidelberg.